Editorial - Mancebo, Deise; Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Feijoo, Ana Maria Lopez Calvo de; Mendes, Deise Maria Leal Fernandes; Prestrelo, Eleonôra Torres; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2011)
Deise Mancebo, Adriana Benevides Soares, Alexandra Cleopatre Tsallis, Ana Maria Lopez Calvo de Feijoo, Deise Maria Leal Fernandes Mendes, Eleonôra Torres Prestrelo, Rita Maria Manso de Barros